Problems of Teaching Technical Sciences: An In-Depth Study (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Teaching technical sciences faces numerous challenges, including the integration of modern technologies, aligning curricula with industry standards, and addressing diverse student needs. This article examines the complexities of technical education, highlighting innovative teaching strategies, the role of practical training, and the impact of digital transformation. Solutions to bridge the gap between theoretical knowledge and real-world application are also discussed.